Neem extract formulations to control diabrotica speciosa (coleoptera: Chrysomelidae) larvae in maize - Boiça Júnior, Arlindo Leal [UNESP]; Costa, Eduardo Neves [UNESP]; De Souza, Bruno Henrique Sardinha; Ribeiro, Zulene Antonio [UNESP]; Costa, Eveline Soares; Forim, Moacir Rossi (SAGE Publications, 2017)
Diabrotica speciosa larvae have been considered to be one of the major subterranean pests of several crops, and its most susceptible host is maize (Zea mays). This study aimed to evaluate the effects of oil-formulated neem extract and lignin-microencapsulated neem extract for D. speciosa larvae control. Effects of applications of neem formulations on the growth of maize plants were also assessed. In the first assay, 0.25, 0.5, 1.0, 2.0, and 4.0 mL of oil-formulated neem extract were applied per 25 g soil and were compared with the insecticide fipronil WG and deionized water. In the second assay, lignin-microencapsulated neem extract was applied at 160, 80, 40, 20 and 10 mg per 25 g soil, and compared with the same controls. Both neem formulations were as efficient as the insecticide fipronil WG in the control of D. speciosa larvae. The evaluated doses of neem formulations did not interfere on maize plants growth. Results of this study permit concluded that, under laboratory conditions, oil-formulated neem extract and lignin-microencapsulated neem extract formulations are promising for controlling D. speciosa larvae in maize, and might benefit sustainable pest management.
Formulaciones de nim para el control de larvas de diabrotica speciosa (coleoptera: Chrysomelidae) en maíz
Keywords: Azadirachta indica; Botanical pesticides; Corn rootworm; Pest management